Hubungan regulasi emosi dengan academic burnout pada santri tahfidz pondok pesantren annuqoyyah latee guluk-guluk sumenep - Mohammad Irsyadil Isbadi; Nasiruddin Al-Ahsani (Psychospiritual: Journal of Trends in Islamic Psychological Research, 2025)
The objective of this research is to examine whether emotion regulation is associated with academic burnout. According to theory, academic burnout is closely related to negative emotions. Emotional regulation is considered a way to overcome academic burnout. In this study, the independent variable of focus is emotional regulation, while the dependent variable is academic fatigue. Academic burnout refers to the theory of Maslach and emotional regulation is based on the theory of Gross. The research method employed is quantitative research with a correlational approach. Using a research sample of 35 students from the Tahntri Tahfidz Islamic boarding school Annuqayyah Latee Guluk-Guluk Sumenep. The sample method used is saturation sampling due to the research population being less than 100 individuals. The data collection technique employed in this study was the use of a research questionnaire with scales for emotional regulation and academic burnout. The Pearson product-moment correlation is used for data analysis in this study. The results of this study indicate that emotional regulation is related to academic burnout in Santri Tahfidz Islamic boarding school Annuqayyah Latee Guluk-Guluk Sumenep, with a Pearson correlation coefficient of -.529. This means that there is a correlation between the emotional regulation variable and the academic burnout variable, with a moderate strength of association. This is based on the guideline categories in the range of 0.41-0.60. As a result, it can be concluded that Ha is accepted and Ho is rejected.